Quantum photovoltaic effect: Two photon process in solar cell - Alp, Dilan (IEEE, 2015)
Photoelectric effect using two photon processes is a new research area interest that referrers to science and technology fields to find out new solar cells. In this review article focuses on examining light-matter interaction in quantum processes which are directly or indirectly related to the photoelectric effect and highlighting recent research results. This model is used as a tool to understand and the theoretical limits of the two-color photovoltaic (TPPV) phenomenon and discussed that are useful generation phtovoltaic (PV) materials which are targeting higher efficiency solar cells. This study will focus on the limitations of current photovoltaic cell devices which are high stability, high efficiency and explore current research for the advancement of solar cell technology the possibilities to improve cell technology.
Keywords: Solar cell; Ligt-matter interaction; Quantum photovoltaic effect; Two photon process